DNase γ, DNase I and caspase‐activated DNase cooperate to degrade dead cells. (22nd September 2016) - Koyama, Ryo; Arai, Tomoya; Kijima, Marie; Sato, Shoko; Miura, Shigetoshi; Yuasa, Makoto; Kitamura, Daisuke; Mizuta, Ryushin
Abstract : Serum endonucleases are essential for degrading the chromatin released from dead cells and preventing autoimmune diseases such as systemic lupus erythematosus. Serum DNase I is known as the major endonuclease, but recently, another endonuclease, DNase γ/DNase I‐like 3, gained attention. However, the precise role of each endonuclease, especially that of DNase γ, remains unclear. In this study, we distinguished the activities of DNase γ from those of DNase I in mouse serum and concluded that both cooperated in degrading DNA during necrosis: DNase γ functions as the primary chromatolytic activity, causing internucleosomal DNA fragmentation, and DNase I as the secondary one, causing random DNA digestion for its complete degradation. These results were confirmed by two in vivo experimental mouse models, in which necrosis was induced, acetaminophen‐induced hepatic injury and streptozotocin‐induced β‐cell necrosis models. We also determined that DNase γ functions as a backup endonuclease for caspase‐activated DNase (CAD) in the secondary necrosis phase after γ‐ray‐induced apoptosis in vivo .